Dukungan Sosial dan Kecerdasan Emosional (Emotional Quotient) dengan Stres di tengah Pandemi Covid-19 pada Masyarakat Cempaka Putih Barat, Jakarta Pusat - Rima Utari R. Sibua; Sondang Maria J. Silaen (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This study is a quantitative study that aims to determine the relationship between social supportand emotional quotient with stress amid the Covid-19 pandemic in the Cempaka Putih WestCentral Jakarta community. The subjects of this study were 110 young adults who lived in WestCempaka Putih with an age range of 20-40 years, using a multistage random samplingtechnique. This study uses three measurement scales, namely the Stress Scale, SocialProvisions Scale (SPS), and Wang and Law Emotional Intelligence Scale (WLEIS). The resultsshowed that there was a significant negative relationship between social support and stress ofr = -0.309 and p = 0.001 (p <0.05). There is a significant negative relationship betweenemotional quotient and stress of r = -0.446 and p = 0.000 (p <0.05). Furthermore, the resultsof data analysis using multivariate correlation using the SPSS (Statistical Product and ServiceSolution) version 25.0 for MAC-windows computer program obtained a correlation coefficientof R = 0.507. The research results conclude that the higher social support, the lower stress isfelt, then if the higher emotional intelligence, the lower stress is felt, and vice versa, the lowersocial support, the higher stress is felt. Social support contributed 25.7% more dominantlythan emotional intelligence which accounted for 19.9% and the remaining 53% was anotherfactor not examined in this study.